Konstruksi Nalar dan Pola Pembacaan Maqāṣid al-Sharī‘ah dalam Filsafat Hukum Islam Ibn Taymīyah - Hijrian Angga Prihantoro (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2018)
This paper aims to track the construction of maqāṣid al-sharī‘ah reasoning and reading patterns of maqāṣid al-sharī‘ah according to Ibn Taymīyah perspective. The study of the philosophy of Islamic Law in the perspective of Ibn Taymīyah in Islamic thought is still not much discussed, even not yet formulated with a comprehensive framework of construction of reason. Maqāṣid al-sharī‘ah in Ibn Taymīyah’s perspective has a reciprocal reading pattern in quadric jalb al-maṣlaḥah and daf‘ al-mafsadah at one time simultaneously. These quadrics here are relational dialectics between min jānib al-wujūd and min jānib al-‘adam. Ibn Taymīyah as one of the most knowledgeable scholars of science has a unique reading pattern on how the legal texts (ayāt al-aḥkām) and their intentions (al-maqāṣid) are dialecticalized.